(untitled) (Bangladesh Journal of Medical Science, 2022)
Objective: This study examines the difference of interference effect in high and low neuroticism. Material and Methods: Low and high groups of neuroticism performed the congruent and incongruent Stroop Colour Word task in the Event Related Potential session. The ERP P300 was extracted and analysed. Results: High neuroticism exhibited larger P300 amplitude than low neuroticism in both congruent and incongruent condition. Conclusion: High neuroticism appraises conflict and non-conflict condition under incompatibility manner driven by prefrontal cortical top–down control. Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 129-134